Analisis Fungsi kakujoshi de dalam Aplikasi Todai Easy Japanese News - Yosi Novita Sari; Rita Arni (Universitas Negeri Padang, 2023)
Analysis the function of kakujoshi de In Today Easy Japanese News Application. Thesis. Padang: Japanese Language Education Study Program, English Language and Literature Department, Faculty of Languages and Arts, Padang State University. In general, joshi can be divided into four types, that are setsuzokujoshi, fukujoshi, kakujoshi, fukujosi, and shuujoshi. Kakujoshi is a particle in Japanese which is a link between noun and predicate. Kakujoshi has various functions and meanings, in a sentence kakujoshi there are several different functions. The researcher appraise that the importance of research analyzes kakujoshi in the Today Easy Japanese News application, so that there is no misunderstanding of students. The aims of this study is to describe the function of kakujoshi in Today Easy Japanese News application. This study uses descriptive qualitative design. The data in this study are sentences that use kakujoshi function in Today Easy Japanese News application according to Sugihartono's theory (2001). The data source in this study is the Today Easy Japanese News application. The instrument of this research is the research itself. Based on the results of the research conducted, researcher found seven functions of kakujoshi de in the Today Easy Japanese News application based on Sugihartono's theory (2001). Kakujoshi function that is not found in Today Easy Japanese News application is the function of showing the “most” at a certain scope/group in revealing something.